Completeness of Delivery and Accuracy of Delivery Diagnosis Code On The Smooth Verification of BPJS Claims in Hospital - Nofri Heltiani; Lolli Nababan; Liza Putri (Greenation International Journal of Tourism and Management, 2023)
The completeness of the files and the accuracy of the diagnostic code have an important role in the smooth verification of claims and are the basis for the approval of fee billing by BPJS to Hospitals. From the results of initial observations of 10 samples of claim files for delivery cases submitted to BPJS, it was found that 4 (40%) files passed verification and 6 (60%) files were pending due to incomplete claim files such as no supporting reports and DPJP signatures and coding information which are not in accordance with BPJS Health, resulting in delays in the claim payment process which causes material losses for the Hospital. The purpose of this study was to determine the completeness of the file and the accuracy of the delivery diagnosis code for the smooth verification of BPJS claims. this type of research is observational with a descriptive design. The population in this study was 137 files with 58 samples taken by simple random sampling which were processed univariately using a frequency distribution. The results of the study were claim files for complete and smooth delivery cases 31(53%), complete claim files but not smooth verification 22(38%) and incomplete claim files and not smooth verification 5(9%), while the delivery diagnosis code was accurate and smooth verification 31(53%), diagnostic codes accurate but verification not smooth 5(9%) and diagnostic codes inaccurate and verification not smooth 22(38%). It is recommended that the Hospital should make efforts to improve the accuracy of the diagnostic code through training, monitoring and regular evaluation to minimize the occurrence of claim returns.